2011
DOI: 10.1111/j.1574-6968.2011.02460.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of cellulose- and cellobiose-degrading soil Bacteria by two acidic herbicides

Abstract: Herbicides have the potential to impair the metabolism of soil microorganisms. The current study addressed the toxic effect of bentazon and 4-chloro-2-methylphenoxyacetic acid on aerobic and anaerobic Bacteria that are involved in cellulose and cellobiose degradation in an agricultural soil. Aerobic saccharide degradation was reduced at concentrations of herbicides above environmental values. Microbial processes (e.g. fermentations, ferric iron reduction) that were linked to anaerobic cellulose and cellobiose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
2
7
0
1
Order By: Relevance
“…It is liable that this herbicide might noxiously affect on the bacterial communities, because in the soil of CONFYM treatment the numbers of total bacteria and cellulose decomposers decreased by 21% and 31%, respectively, as compared with the ORGFYM treatment. Our results are similar to the results of Schellenberger et al (2012) who reported about the toxic effect of MCPA on the cellulose degrading bacteria in the water-saturated soil. Such moisture conditions existed in 2010 because during August and September it rained the total of 243 mm.…”
Section: Resultssupporting
confidence: 83%
“…It is liable that this herbicide might noxiously affect on the bacterial communities, because in the soil of CONFYM treatment the numbers of total bacteria and cellulose decomposers decreased by 21% and 31%, respectively, as compared with the ORGFYM treatment. Our results are similar to the results of Schellenberger et al (2012) who reported about the toxic effect of MCPA on the cellulose degrading bacteria in the water-saturated soil. Such moisture conditions existed in 2010 because during August and September it rained the total of 243 mm.…”
Section: Resultssupporting
confidence: 83%
“…It is liable that this herbicide might noxiously affect the bacterial communities because, in the soil of this system, the soil microbial biomass decreased. Our results are similar to the results of other researchers, who have reported on the toxic effect of MCPA on bacteria [25] and soil enzymatic activity [22]. Previous studies revealed the adverse impacts of pesticides on soil microbial biomass [26,27].…”
Section: Biological Soil Propertiessupporting
confidence: 92%
“…Cellulose becomes metabolized in soil through the presence of abundant aerobic and anaerobic cellulolytic microorganisms (Schellenberger et al, 2012). Over the initial three days of our bioassay, nicosulfuron caused no change in the abundance of cellulolytic microorganisms in loamy soil (Table 2).…”
Section: Resultsmentioning
confidence: 97%